Combined shearography and speckle pattern photography for single-access multi- component surface strain measurement - Groves, Roger M.; James, Stephen W.; Tatam, Ralph P.; Fu, S. (International Society for Optical Engineering; 1999, 2003)
Full surface strain measurement requires the determination of two out-of-plane and four in-plane displacement gradient components of the surface strain tensor. Shearography is a full-field speckle interferometry technique with a sensitivity predominately to the out-of-plane displacement gradient. Speckle pattern photography has the sensitivity to the in-plane displacement, and taking the derivative yields the in-plane displacement gradient. In this paper the two techniques are combined to yield a single-access multi-component surface strain measurement using shearography to measure the out-of-plane components and speckle pattern photography to measure the in-plane components. Results are presented of a multi-component surface strain measurement.
Keywords: Shearography; Speckle Pattern Photography; Surface Strain Measurement